Size-Dependent Interplay of Volume Exclusion Versus Soft Interactions: Cytochrome c in Macromolecular Crowded Environment - Parray, Zahoor Ahmad; Ahmad, Faizan; Chaudhary, Anis Ahmad; Rudayni, Hassan Ahmad; Al-Zharani, Mohammed; Hassan, Md. Imtaiyaz; Islam, Asimul (Frontiers in Molecular Biosciences, 2022)
Even though there are a great number of possible conformational states, how a protein generated as a linear unfolded polypeptide efficiently folds into its physiologically active form remained a fas-cinating and unanswered enigma inside crowded conditions of cell. In this study, various spectro-scopic techniques have been exploited to know and understand the effect and mechanism of action of two different sizes of polyethylene glycols, PEGs (molecular mass ~ 10 and ~20 kilo Daltons, kDa) on cytochrome c (cyt c). The outcomes showed that small size PEG leads perturbation of the protein structure, and conversely, large size of PEG has stabilizing effect on cyt c. Moreover, binding measurements showed that small size of PEG interacts strongly via soft interactions compared to the larger size of PEG, later is governed more by excluded volume effect or preferential exclusion from the protein. Overall, this finding suggests that conformations of protein may be influenced in cellular crowded conditions via interactions which depend upon the size of molecule in the environment. This study proposes that both volume exclusion and soft (chemical) interactions governs protein’s conformation and functional activities. Cellular environment's internal architecture as evident by crowder size and shape in this study has significant role.